Theorizing surveillance and social spacing through football: The fan‐opticon and beyond. Issue 2 (3rd December 2022) - Turner, Mark; Lee Ludvigsen, Jan Andre
Abstract: This article critically examines the temporal mobilizations of a 25‐year football supporter social movement against the all‐seating (stadia) legislation in England and Wales, to unpack, and advance, (neo‐)Foucauldian panoptic theorizations of surveillance power and counter‐power. Drawing upon prior empirically informed analysis of this movement; 'Safe Standing', the article interrogates new policy‐based outcomes, including the early adoption of 'licensed (Safe) Standing' technology in 2022, to argue, that whilst publicly framed as a movement victory, it simultaneously serves to prefigure a new regulatory regime in football; one which extends the regulation and surveillance of fans within the wider social and corporate lifeworld . Introducing our new concept; the 'fan‐opticon', the article discusses how Safe Standing continues to normalize a momentum of surveillance in sport and highlights the contradictory nature of security‐related projects in the twenty‐first century. We conclude that the governmentality of the state through football, to be characteristic of temporally sensitive hermeneutic struggles of power and resistance, through the discipline, and self‐discipline of social actors. New forms of subjectivity are remoulded in ways which extend the power of surveillance and regulation, despite multiple counter‐conduct, and discursive, resistance practices.